PENGARUH E-PRODUCT KNOWLEDGE, E-SOCIAL INFLUENCE, DAN E-TRUST TERHADAP KEPUTUSAN BERDONASI DI APLIKASI KITABISA.COM - Nanda Della Fitriana; Hamdan Hamdan; Erna Sofriana Imaningsih (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- Technology is currently experiencing very rapid development and improvement, thus forming an innovation in the field of financial technology, one of which is the crowdfunding system. This crowdfunding innovation is used as a means of social, humanitarian and handling of victims of natural disasters. One of the platforms that uses the crowdfunding system in Indonesia is Kitabisa.com. The purpose of this study was to examine and analyze the effect of e-product knowledge, e-social, and e-trust knowledge on the decision to donate using Kitabisa.com. The subjects of this research are people who know or have used this Kitabisa.com. The sample used in this study amounted to 145 respondents. The sampling technique was carried out using a purposive sampling method using a quantitative research design. The data analysis used was statistical analysis in the form of SEM-PLS. The results of this study indicate that e-product knowledge, e-social influence, and e-trust have a positive and significant impact on the decision to donate. Keywords: e-decision to Donate; e-social Influence; e-product Knowledge; e-trust; kitabisa.com